Prognostic significance of Epstein–Barr virus DNA in NK/T-cell lymphoma: a meta-analysis - Fei, Qian (Onco Targets Ther, 2018)
Extranodal NK/T-cell lymphoma is closely associated with Epstein–Barr virus (EBV) infection. However, the prognostic value of EBV-DNA in extranodal NK/T-cell lymphoma remains unclear. Thus, we conducted a meta-analysis to estimate its prognostic significance. PubMed, EMBASE, and Web of Science were used to search for studies conducted until June 12, 2017. The pooled hazard ratio (HR) and its 95% confidence interval (CI) were calculated to evaluate the prognostic value of pretreatment EBV-DNA on the overall survival of extranodal NK/T-cell lymphoma. Seven eligible studies on 356 patients with extranodal NK/T-cell lymphoma were pooled for this meta-analysis. Results suggested that the pretreatment EBV-DNA positivity was significantly correlated with the overall survival of extranodal NK/T-cell lymphoma (pooled HR =3.78, 95% CI: 1.52–9.40, p=0.004; heterogeneity test: I(2)=52%, p=0.05). Subgroup analyses stratified by sample type, survival analysis mode, and HR origin showed that patients with positive pretreatment EBV-DNA had poorer prognosis than those with negative pretreatment EBV-DNA. Moreover, the cut-off value (HR =1.66; 95% CI: 0.73–3.73; p=0.22) might account for the heterogeneity. No significant publication bias was observed. Pretreatment EBV-DNA positivity can predict poor prognosis for patients with extranodal NK/T-cell lymphoma. Future large-scale studies based on prognostic significance of EBV-DNA for patients with extranodal NK/T-cell lymphoma are necessary.